2015
DOI: 10.1123/ijspp.2014-0103
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Physical Performance in Elite Junior Tennis Players With a Caffeinated Energy Drink

Abstract: The aim of this study was to investigate the effectiveness of a caffeinated energy drink to enhance physical performance in elite junior tennis players. In 2 different sessions separated by 1 wk, 14 young (16 ± 1 y) elite-level tennis players ingested 3 mg caffeine per kg body mass in the form of an energy drink or the same drink without caffeine (placebo). After 60 min, participants performed a handgrip-strength test, a maximal-velocity serving test, and an 8 × 15-m sprint test and then played a simulated sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 25 publications
0
52
0
1
Order By: Relevance
“…The duration and degree of the standardization protocols differed among studies. The duration whereby participants had to abstain from all dietary sources of alcohol, caffeine and other stimulants ranged from the day itself [36,40] to 24 hours [35][36][37][41][42][43][44][45], 48 hours [34,38,39,[46][47][48][49][50] and the entire study duration (2 sessions separated by 1 week) [51]. Participants were also asked to adopt a similar diet and fluid intake level the day before each experimental trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration and degree of the standardization protocols differed among studies. The duration whereby participants had to abstain from all dietary sources of alcohol, caffeine and other stimulants ranged from the day itself [36,40] to 24 hours [35][36][37][41][42][43][44][45], 48 hours [34,38,39,[46][47][48][49][50] and the entire study duration (2 sessions separated by 1 week) [51]. Participants were also asked to adopt a similar diet and fluid intake level the day before each experimental trial.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were also asked to adopt a similar diet and fluid intake level the day before each experimental trial. Several studies also included a pre-competition meal either 2 [46] or 3 hours before each trial to mimic their habitual routines [35,36,40,44,48,49,51]. In terms of activity levels, participants were advised to avoid all strenuous exercise the day before each trial to minimize any muscle soreness and fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…The GPS underestimated the distance covered, mean speed and peak speed during court-based tennis movements and showed a low to high intraclass coefficient of correlation (ICC = 0.1 to 0.86) and a low to high coefficient of variation (CV = 3.5 to 22.8) (Duffield et al, 2010; Scott et al, 2015; Vickery et al, 2014). In a recent study, the GPS units were sensitive enough to detect locomotor activity changes in response to caffeinated energy drink ingestion in comparison to placebo (Gallo-Salazar et al, 2015). The acceleration profile was also used as a parameter of performance during the matches.…”
Section: Methodsmentioning
confidence: 99%
“…Few recent studies reported an improvement in physical performance in junior tennis players [46] and adolescent basketball players [41] . Although the US Food and Drug Administration limits caffeine content in soft drinks, which are categorized as food, there is no such regulation for energy drinks, which are classified as dietary supplements.…”
Section: Role Of Caffeine and Caffeinated Energy Drinks On Physical Pmentioning
confidence: 99%